Volunteering via Smart-Phone for People With Psychosis—Protocol of a Feasibility Trial - Pinto da Costa, Mariana; Phone Pal Advisory Groups, (Frontiers in Psychiatry, 2021)
The literature suggests that volunteering can be used to address social isolation and support patients with psychosis in the community. However, many expect in person meetings, requiring a greater effort of availability and commitment. There is therefore a need for more flexible, easily accessible support. Volunteering via smart-phone could be a useful intervention for people with psychosis. One patient and one volunteer have been matched for the 12-week study duration, and participants have been encouraged to communicate through a variety of communication methods (audio calls, video calls, text messages, WhatsApp messages and e-mails). The Phone Pal study has aimed to investigate the feasibility of recruitment, participant retention, data collection procedures, intervention usage in terms of the methods of communication and changes in outcome data. At baseline and follow-up outcome measures collected from patients and volunteers include their quality of life, physical activity, self-esteem and social comparison. Additional outcomes assessed encompass patients’ attachment, social contacts and symptoms; for volunteers, their social distance has been evaluated. At follow-up both patients and volunteers rank their perception of their relationship with each other. This mixed method feasibility study has been conducted in two phases, the first stage evaluating a smaller sample of patients and volunteers recruited in London, and then a second phase with a larger sample of volunteers recruited from across the United Kingdom. Trial registration: ISRCTN17586238